Current insights of applying MRI in Graves’ ophthalmopathy - Song, Cheng; Luo, Yaosheng; Yu, Genfeng; Chen, Haixiong; Shen, Jie (Frontiers in Endocrinology, 2022)
Graves' ophthalmopathy (GO) is an autoimmune disease related to Grave’s disease (GD). The therapeutics strategies for GO patients are based on precise assessment of the activity and severity of disease. However, current assessment system is in need of development to accommodate updates in treatment protocols. As an important assistant examination, magnetic resonance imaging (MRI) can help physicians to evaluate GO more accurately. With the continuous updating of MRI technology and the deepening understanding of GO, the assessment of this disease by MRI has gone through a stage from qualitative to precise quantification, making it possible for clinicians to monitor the microstructural changes behind the eyeball and better integrate clinical manifestations with pathology. In this review, we use orbital structures as classification to combine pathological changes with MRI features. We also retrospect some MRI techniques that have been applied to GO clinical practice such as disease classification and regions of interest selection.